Pyogenic Liver Abscess Caused by Endoscopic Submucosal Dissection for Early Colon Cancer - Joon Seop Lee; Yong Hwan Kwon (Korean Society of Gastrointestinal Endoscopy, 2019)
Endoscopic submucosal dissection (ESD) is widely used for the treatment of colorectal neoplasia in patients who are candidates for endoscopic resection. In particular, pyogenic liver abscess (PLA), although rare, can occur. To our knowledge, there are no reports of PLA cases after ESD. Therefore, we report a rare case of PLA caused by ESD. A 76-year-old man was referred from a local clinic and admitted to our hospital for colonic ESD for a large polypoid mass. During colonoscopy, a 5-cm mass was seen in the cecum. ESD was performed. Four days after the procedure, he complained of myalgia and abdominal discomfort. Computed tomography revealed a 5.4-cm PLA in the medial segments of the liver. He was treated with antibiotics, and a percutaneous drainage catheter was inserted. Here, we report a very rare complication (PLA) after ESD. In conclusion, comprehensive awareness of the development of PLA is needed in ESD cases.